De Guerras y de Dagas: crédito y parentesco en una familia limeña del siglo XVII - Espinoza, Augusto (2013)
This article analyzes the nature of economic relations which began with the use of credit. In particular, it will study an important seventeenth century limanian family: the Guerra de la Daga. Two members of that family, Lucía and Clara, founders of the monastery of Santa Catalina in Lima, invested their capital in that monastery and guarantied its autonomy with respect to the administration of convent goods. To insure their control, they saturated the patrimony of their brother Antonio, owner of a mayorazgo, with different loans. This situation redefined family relationships between the founding abbesses and their brothers and descendants.